Degrees of freedom : punishment, personal life and place in Dublin's North Inner City - Breen, Jessica D. (Trinity College (Dublin, Ireland). School of Social Work and Social Policy, 2010)
This thesis presents the findings of a four year research project exploring the experience and meaning of punishment in Dublin’s North Inner City, a place which is home to many ex-prisoners as well as current prisoners serving sentences in a number of prisons. The aim of this thesis is to describe and understand the role of punishment as a social institution in the personal and social lives of those living in this area. This thesis draws on several intellectual traditions within sociology, primarily the sociology of punishment, along with strands of the sociologies of personal life and place. It argues that within the sociology of punishment there is much to be gained by studying understandings of punishment intensively and in context. This thesis aims to provide a theoretically nuanced and empirically rich account of the various ways in which punishment operates in everyday life; it does this by taking a micro-approach to the macro-realities of socio-economic segregation, disproportionate disadvantage, and spatially concentrated imprisonment.
Keywords: Social Work and Social Policy, Ph.D.; Ph.D. Trinity College Dublin